Faktor Keterlambatan Pekerjaan Struktur Gedung terhadap Biaya Pelaksanaan pada Proyek Pembangunan Hotel di Bekasi - Dian Dwi Putra; Ninik Paryati; Elma Yulius (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2019)
Nowadays, delays in project often occur and cause various losses both for service providers and users. For the contractors, delays create the project cost overruns due to project overtime and can decrease contractor credibility in the future. This study aims to analyze a project delay by minimizing the work delays earlier. The analysis of a hotel building planning regarding the cost and time delays is done qualitatively by distributing questionnaires to the contractors and processing the responses using the SPSS software. The results of the S curve analysis and 30 factors that caused the project delay were identified and indicated that there was a delay value of 1.26% with five variables that most contributed to the delay in the construction project at PT. Wijaya Kusuma Contractors, i.e. reworking due to construction errors, low coordination between contractors and stakeholders, late material delivery, and equipment shortages.